Causal role of immune cells in Hashimoto’s thyroiditis: Mendelian randomization study - Zhao, Zhendan; Gao, Yuehua; Pei, Xiaoqing; Wang, Wenhao; Zhang, Huawei (Frontiers in Endocrinology, 2024)
Objectives: Hashimoto's thyroiditis (HT) is a common autoimmune disease whose etiology involves a complex interplay between genetics and environment. Previous studies have demonstrated an association between immune cells and HT. However, the casual relationship was not clear. We aimed to explore the causal associations between signatures of immune cell and HT.Methods: In this study, bidirectional two-sample Mendelian randomization (MR) analysis was conducted to investigate the potential causal relationship between 731 immune cell signatures and HT by using genome-wide association study (GWAS) data. Heterogeneity and horizontal pleiotropy were detected through extensive sensitivity analyses.Results: The increased levels of six immune phenotypes were observed to be causally associated with increased risk of HT (P<0.01), that were CD3 on CM CD8br, CD3 on CD39+ secreting Treg, HLA DR on CD33dim HLA DR+ CD11b-, CD3 on CD4 Treg, CD62L-plasmacytoid DC %DC, CD3 on CD45RA+ CD4+. Besides, the levels of FSC-A on HLA DR+ T cell and CD62L on monocyte were associated with disease risk of HT (P<0.01). In addition, HT also had causal effects on CD3 on CM CD8br, CCR2 on monocyte, CD25 on CD39+ resting Treg, CCR2 on CD62L+ myeloid DC (P<0.05).Conclusions: In this study, we demonstrated the genetic connection between immune cell traits and HT, thereby providing guidance and direction for future treatment and clinical research.